circ-0001875 downregulation is associated with M1 macrophage activation and lung inflammation in severe asthma - Liu, Gege; Cao, Jiahao; Lin, Yiyan; Long, Bingyu; Su, Yanyu; Qiu, Guiqiang; Jiang, Chi; Wang, Yue; Zhao, Xuanna; Huang, Dan; Wu, Dong (Frontiers in Immunology, 2025)
BackgroundAsthma is a heterogeneous group of diseases. The mechanism by which dysregulated circRNAs affect severe asthma by regulating macrophage polarization remains unclear.MethodsHigh-throughput RNA sequencing technology was used to analyze circRNA expression in peripheral blood mononuclear cells (PBMCs) from patients with severe asthma. RT-qPCR and ELISA were used to analyze the expression of inflammatory factors in a mouse model of severe asthma induced by ovalbumin-lipopolysaccharide. The effect of circ-0001875 on macrophage activation and the underlying mechanism were analyzed by RT-qPCR, Western blot, and ELISA. Subsequently, the regulatory relationships among circ-0001875, miR-31-5p, and SP1 were examined through dual luciferase reporter gene assay, and the mechanism by which they regulate macrophage polarization was analyzed by Western blot.ResultsCompared with the healthy control group, 420 circRNAs were differentially expressed in PBMCs from patients with severe asthma. Among them, circ-0001875, which was mainly expressed in the cytoplasm of monocytes, was significantly downregulated in asthmatics, especially those with severe disease. circ-0001875 overexpression inhibited M1 macrophage activation in vitro and alleviated lung inflammation in a mouse model of severe asthma. Mechanistically, circ-0001875 promoted SP1 translation by competitively binding to miR-31-5p, thereby reducing its inhibitory effect on SP1 translation; SP1 then inhibited M1 macrophage polarization, which is associated with severe asthma, through the NF-κB signaling pathway.ConclusionsWe found that circ-0001875 plays an important role in regulating M1 macrophage polarization, which is associated with a severe pro-inflammatory response.